Solidaritas Sosial Masyarakat Beriman di Desa Penambuhan Kabupaten Pati Pada Masa Pandemi COVID-19 - Prastika, Jasmiatun Lynnda; Farihah, Irzum (Advances in Humanities and Contemporary Studies, 2023)
The phenomenon during the COVID-19 pandemic experienced by the community is influential in life, especially social conditions facing change. This phenomenon is found in the faithful community of Penambuhan Margorejo Pati Village during the COVID-19 pandemic which experienced a reduction in social solidarity. The purpose of this article is to describe and find out the social solidarity that occurred in Penambuhan Village during the COVID-19 period. This study uses a qualitative method, where the researcher conducts interviews with the people concerned, such as people who are exposed to COVID-19, people who are not exposed, families of patients with COVID-19, and community leaders in Penambuhan Village.The results of the study focus on two important points. First, the views of the faithful regarding social solidarity in Penambuhan Village during the COVID-19 pandemic. There has been a lack of social solidarity in the community of faith, where people who have been exposed to COVID-19 are shunned and even ostracized by their neighbors. As a community of faith, we should help each other to our fellow human beings as a form of acts of faith. Second, the main cause of the problem of social solidarity of the faithful in Penambuhan Village during the COVID-19 pandemic, namely the negative stigma from the community regarding COVID-19, a very dangerous type of virus that can cause death. In addition, people who are not exposed to COVID-19 stay away from people who are exposed because they have excessive anxiety and are very afraid of contracting it.